Financial investigation and forensic accounting - Manning, George A. (Boca Raton, Fla. : CRC Press, 1999)
Financial Investigation and Forensic Accounting offers a thorough examination of current methods and legal concerns for the detection and prosecution of economic crime. The book guides law enforcement and prosecutors from detection, through indictment and conviction. The author explains the mechanics of gambling, fraud and money laundering. He illustrates how prosecutors present the tax codes, off-shore banking laws, and the RICO statutes to judges and juries.
Includes bibliographical references (p. 459-461) and index.
oif 10/03/15
Loan
Keywords: Forensic accounting -- United States; White collar crime investigation -- United States; Fraud investigation -- United States